2002
DOI: 10.1097/00000542-200206000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Prolongs Local Analgesia after Subcutaneous Infiltration of Bupivacaine Microcapsules in Human Volunteers

Abstract: Addition of small amounts of dexamethasone to bupivacaine incorporated in microcapsules prolonged local analgesia compared with microcapsules with plain bupivacaine after subcutaneous administration in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 0 publications
4
49
1
Order By: Relevance
“…Dexamethasone, a high-potency, long-acting glucocorticoid with little mineralocorticoid effect, has been shown to prolong peripheral nerve blockade in animals [5][6][7][8] and, when added to bupivacaine microspheres, to extend the duration of analgesia in humans [9,10]. Although incompletely understood, dexamethasone's mechanism of action may stem from decreased nociceptive C-fibre activity via a direct effect on glucocorticoid receptors [11] and inhibitory potassium channels [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone, a high-potency, long-acting glucocorticoid with little mineralocorticoid effect, has been shown to prolong peripheral nerve blockade in animals [5][6][7][8] and, when added to bupivacaine microspheres, to extend the duration of analgesia in humans [9,10]. Although incompletely understood, dexamethasone's mechanism of action may stem from decreased nociceptive C-fibre activity via a direct effect on glucocorticoid receptors [11] and inhibitory potassium channels [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous approaches to prolonged-duration local anesthesia have been investigated in animal models 3Y11 and in humans. 6,9,10,12,27,28 We believe that site 1 sodium-channel toxins have several potentially attractive features as candidates for prolonged-duration local anesthesia. They appear to produce far less neurotoxicity or myotoxicity 28 than amino-amide local anesthetics such as lidocaine or bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…203 Holte and colleagues found that in human volunteers receiving subcutaneous injections, the "area under the curve" analgesic benefi ts from 1 to 7 days after a 10-mL subcutaneous injection were significantly better for the treatment group receiving dexamethasone. 204 In this study, dexamethasone comprised 0.04% of microsphere weight, and a dose of 50-µg dexamethasone was injected. 204 Kopacz and colleagues found that in human volunteers receiving intercostal nerve blocks, participants receiving dexamethasone-laden bupivacaine microspheres had block durations ranging from 18 to 30 hours versus shorter durations in the nondexamethasone microsphere group (8 to 16 hours) and aqueous injection group (5 to 7 hours).…”
Section: Buprenorphine and Clonidinementioning
confidence: 99%
“…204 In this study, dexamethasone comprised 0.04% of microsphere weight, and a dose of 50-µg dexamethasone was injected. 204 Kopacz and colleagues found that in human volunteers receiving intercostal nerve blocks, participants receiving dexamethasone-laden bupivacaine microspheres had block durations ranging from 18 to 30 hours versus shorter durations in the nondexamethasone microsphere group (8 to 16 hours) and aqueous injection group (5 to 7 hours). 205 In the fi rst human trial of the coadministration of dexamethasone with aqueous local anesthetic (lidocaine), Movafegh and associates recently reported that nerve block duration was increased by 2.4-fold (98 to 130 minutes with plain lidocaine vs. 242 to 310 minutes with added dexamethasone, for sensorymotor blocks, respectively).…”
Section: Buprenorphine and Clonidinementioning
confidence: 99%
See 1 more Smart Citation